RELATIONSHIP BETWEEN GENDER, TRYPTOPHAN AND VITAMIN B3 CONSUMPTION PATTERNS WITH EMOTIONAL EATING IN OVERWEIGHT ADOLESCENTS - Kinanthi Dewi Mutiek; Mohammad Fanani; Adi Magna Patriadi Nuhriawangsa (Universitas Airlangga, 2021)
Emotional eating is the propensity to eat in response of negative emotions such as stress, anxiety and depression. Adolescents with overweight may experience an increase in leptin levels as well as disruption of serotonin resulting in disruption of sensitivity in regulating appetite and emotions, thereby causing emotional eating. Emotional eating can be aff ected by several factors including gender and fulfi llment of nutrients such as tryptophan and vitamin B3 as substances that help the production of serotonin in the body. This study aimed to examine the relationship between gender, tryptophan and vitamin B3 consumption patterns with emotional eating in overweight adolescents. This was cross sectional study in adolescents ranges 15–18 years with overweight or obesity status in Surakarta. In total 122 adolescents taken by purposive sampling method. Emotional eating data were obtained from the Eating and Appraisal Due to Emotions and Stress (EADES) questionnaire while the consumption patterns data were obtained using Food Frequency Questionnaire (FFQ). This study that there was a relationship between tryptophan consumption pattern with emotional eating in overweight adolescents, but there was no relationship between gender and vitamin B3 consumption pattern with emotional eating in overweight adolescents. It can be concluded that there was a relationship between Tryptophan consumption pattern with emotional eating in overweight adolescents and there was no relationship between gender and vitamin B3 consumption pattern with emotional eating in overweight adolescents.